2005
DOI: 10.1111/j.1572-0241.2005.41348.x
|View full text |Cite
|
Sign up to set email alerts
|

Food-Specific Serum IgG4 and IgE Titers to Common Food Antigens in Irritable Bowel Syndrome

Abstract: Serum IgG4 antibodies to common foods like wheat, beef, pork, and lamb are elevated in IBS patients. In keeping with the observation in other atopic conditions, this finding suggests the possibility of a similar pathophysiological role for IgG4 antibodies in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 26 publications
6
66
0
5
Order By: Relevance
“…At the current level of knowledge, determining the concentration of IgG in the serum of patients with IBS is not justified. Results obtained in this study confirm reports by other authors, both those already published in the 1990s [9][10][11], and the latest [12,13], although some researchers have recognized the benefits of testing serum IgG concentration in IBS patients [14][15][16]. Kruszewski et al [10,11] also found that elevated levels of IgG are equally common in healthy people and people who are allergic.…”
Section: Discussionsupporting
confidence: 82%
“…At the current level of knowledge, determining the concentration of IgG in the serum of patients with IBS is not justified. Results obtained in this study confirm reports by other authors, both those already published in the 1990s [9][10][11], and the latest [12,13], although some researchers have recognized the benefits of testing serum IgG concentration in IBS patients [14][15][16]. Kruszewski et al [10,11] also found that elevated levels of IgG are equally common in healthy people and people who are allergic.…”
Section: Discussionsupporting
confidence: 82%
“…Th e primary role of B cells is to produce antibodies (Ig) directed against antigen, and IgG-positive B cells are increased in the blood of IBS patients relative to healthy subjects ( 68 ). Increased blood IgE and IgG concentrations are classically associated with allergy and are typically unaltered in IBS at baseline; however, in response to allergen serum IgE and IgG levels increase in IBS patients above that observed in health ( 37,70,71 ). Interestingly, increased levels of autoantibodies against neuronal channels have been observed in IBS patients; however, the clinical implications of this are yet to be determined ( 105,106 ).…”
Section: B Cellsmentioning
confidence: 99%
“…It is hypothesized that mucosal immune activation by FAs may contribute to the development of food allergy and IBS [9,11,13,[15][16][17]21,25] . Clinically, the role of food-intolerance-induced symptoms in IBS frequently contrasts with that in food allergy [20,[22][23][24][25]29,[37][38][39][40][41][42] , and dietary elimination may be associated with symptom improvement [31] . However, the interaction of food with the gastrointestinal system is not completely understood [13,17,20,22,23,25,29,[33][34][35][36][37]39] .…”
Section: Discussionmentioning
confidence: 99%